2007
DOI: 10.1097/brs.0b013e31814b851f
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Brace Treatment Versus Observation Alone in Adolescent Idiopathic Scoliosis

Abstract: The curves of patients with adolescent idiopathic scoliosis with a moderate or smaller size at maturity did not deteriorate beyond their original curve size at the 16-year follow-up. No patients treated primarily with a brace went on to undergo surgery, whereas 6 patients (10%) in the observation group required surgery during adolescence compared with none after maturity. Curve progression was related to immaturity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
136
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(149 citation statements)
references
References 39 publications
8
136
0
5
Order By: Relevance
“…Long-term follow up of patients with idiopathic scoliosis has demonstrated more thoracic and lumbar back pain and degenerative disc disease [8,54]. Danielsson et al [8] followed 127 patients 22 years after brace treatment and found degenerative lumbar disc changes were more common than in control subjects.…”
Section: Natural Historymentioning
confidence: 99%
See 3 more Smart Citations
“…Long-term follow up of patients with idiopathic scoliosis has demonstrated more thoracic and lumbar back pain and degenerative disc disease [8,54]. Danielsson et al [8] followed 127 patients 22 years after brace treatment and found degenerative lumbar disc changes were more common than in control subjects.…”
Section: Natural Historymentioning
confidence: 99%
“…Danielsson et al [8] followed 127 patients 22 years after brace treatment and found degenerative lumbar disc changes were more common than in control subjects. Additionally, brace-treated patients had more back pain than the control group; however, there was minimal functional impairment or impact on daily life.…”
Section: Natural Historymentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment of mild idiopathic scoliotic curves (Cobb angle 20°-40°) during growth to halt progression is a classic conservative orthopaedic domain [1]. However, bracing as the cornerstone of this strategy remains controversial, as its effect is limited by non-compliance and potential negative psychosocial effects [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%